Emotional contagion of distress in young pigs is potentiated by previous exposure to the same stressor - Goumon, Sébastien; Špinka, Marek (Animal cognition, 2016)
This study tested whether emotional contagion occurs when piglets directly observe a penmate in distress (restraint) and whether there is an effect of previous experience on the response to subsequent restraint or exposure to conspecific distress. Piglets (49.7 ± 0.7 days) were exposed in pairs to two stress phases (SP1 and SP2) in an arena divided into two pens by a wire mesh wall. During SP1, one of the pigs of a pair was either restrained (Stress treatment) or sham-restrained (Control treatment), while the other pig was considered observer. During SP2, the previous observer was restrained, while its penmate took the observer role. Heart rate variability, locomotion, vocalizations, body/head/ear and tail postures were monitored. During SP1, observer pigs responded to conspecific distress with increased indicators of attention (looking at, proximity to and snout contacts with the distressed pigs) and increased indicators of fear (reduced locomotion, increased freezing). During SP2, the observer pigs that had been restrained previously reacted more strongly (through higher proximity, decreased locomotion, increased freezing) to observing the penmate in restraint than pigs without the previous negative experience. This study suggests that young pigs are susceptible to emotional contagion and that this contagion is potentiated by previous exposure to the same stressor. These findings have implications for pig welfare in practical animal husbandry systems.
Keywords: psychický stres; Empathy; vokalizace zvířat; postura těla; mužské pohlaví; Welfare; Sus scrofa; Stress, Psychological; Heart Rate; srdeční frekvence; Heart rate variability; ženské pohlaví; Locomotion; zvířata; Behaviour; Posture; Emotional contagion; emoce; empatie; Emotions; Female; Vocalization, Animal; lokomoce; Male; Animals